Kebijakan dan Tata Kelola Maritim Provinsi Kepulauan Riau Menuju Poros Maritim Dunia - Chaereyranba Sholeh; Fitri Kurnianingsih; firman firman; okky rizki azizi; Ramadhani Setiawan (Jurusan Administrasi Publik FISIP UIN SGD Bandung, 2023)
The purpose of this research is to analyze the implementation of Maritime Policy and Management of the Riau Archipelago Province Towards a World Maritime Axis and analyze the implementation of maritime sector management by the Regional Government of the Riau Islands Province after the enactment of Law Number 23 of 2014 concerning Regional Government and explain the process of solving problems in the maritime sector according to regulations set by the central government and the Riau Islands Provincial government. In the governance of the maritime sector, the Government of Indonesia has various roles which can be seen from the enforced policies or regulations. The complexity that occurs at the central government level is one of the reasons this research was taken which shows the urgency of the need for governance of the maritime sector in Indonesia. Furthermore, after the implementation of decentralization in Indonesia, with the enactment of Law Number 23 of 2014 concerning Regional Government, the management of the maritime sector has become increasingly complex. Data analysis through qualitative research methods with descriptive analysis methods. The results of this study found that, in the initiation of integrated maritime governance in the Riau Archipelago Province, the factors that need to be considered are authority, leadership, visioning, institutional capacity, human resource development, empowerment, and financial resource management. In this study, researchers provide recommendations for the establishment of regulations governing the authority and management of the maritime and island areas. The next phase can be analyzed in further research: planning, adoption, implementation, evaluation, and reformulation.